Group formation and empowerment: the case of brac and proshika in Bangladesh - Moniruzzaman, Md. (IIUM Press, 2007)
This study analyses the group formation process followed by Brac and Proshika in Bangladesh. Based upon field observation and interviews, it is apparent that the process of Brac and Proshika’s group formation suffers from internal contradiction in setting group objectives. The NGOs expect the groups to remain principally focused on social and political change, but the group members’ objective is to access credit from NGOs and gain economic benefit. The NGO workers remain almost detached from the process and remain unaware of the real group objectives. This produces a gap between the expectations of the NGOs and the offstage negotiated objectives of the groups. Despite this contradiction, the group approach clearly demonstrates the achievement of some desired empowering effects but not through the desired ways of the NGOs. Paying closer attention to the group formation process will help NGOs achieve their desired objectives better.